Pengembangan Lembar Kerja Peserta Didik Berbasis Etnosains Pada Mata Pelajaran IPA untuk Meningkatkan Keterampilan Berpikir Siswa Di SMP Negeri 15 Bengkulu Utara - May Wulan Sari; Andang Sunarto; Ahmad Walid (Jurnal Ilmiah Wahana Pendidikan, 2022)
Development or research and development is a research method used to produce certain product, and test the effectiveness of these products. R&D serves to validate and develop products. The purpose of this research is to determine feasibility and effectiveness LKPD. The type of research used is the development of Borg and Gall developed by Sugiono with stages consisting of potential problems, information gathering, initial product & product design, design validation, design revision, product trial small group product revision, final product. The result of developing ethnoscience based student worksheets for eligibility are linguistic experts 86,67%, material experts 94,54%, and media experts 100%. While the result of developing student worksheets based on ethnoscience for effectiveness using the N-Gain test, students experience improvement of students thinking skills on the criteria of high 0,75, medium 0,5, and low 0,25. Small-scale trials were conducted on 10 student of class VII A. The feasibility of developing ethnoscience based student worksheets to improve students thinking skills based on expert validators, the results were qualified and valid so that they could be used for students. While the effectiveness of ethnoscience based student worksheets on the eyes science lessons to improve students thinking skill based on N-Gain are effective for students to use.Key : Ethnoscience, student worksheets, environmental pollution, development.